Genome-Wide Genomic Analysis and Evolutionary Insights into Bovine Coronavirus Strains in Southwest China - Qingqing Li; Huili Bai; Yan Pan; Yuying Liao; Zhe Pei; Cuilan Wu; Chunxia Ma; Zhongwei Chen; Changting Li; Yu Gong; Jing Liu; Yangyan Yin; et al. (Veterinary Sciences)
The global epidemic of bovine coronavirus (BCoV) has caused enormous economic losses. The characterisation and genetic composition of endemic strains in Southwest China remain elusive. This study aimed to fill this gap by isolating three BCoV strains from this region and sequencing their whole genomes. To elucidate the genetic evolution and characterisation of the prevalent strains, the results of BCoV sequences were compared in GenBank, with a focus on genetic evolution, mutation, and recombination patterns. The results showed close homology between strains NN190313 and NN230328, while strain NN221214 showed less similarity to these two strains but clustered with the French strain of the European branch. Intriguingly, NN190313 and NN230328 were grouped with goat-derived BCoV strains from Jiangsu Province in Eastern China in the Asian–American branch. In addition, recombination analyses revealed significant signals between NN230328 and either a Chinese goat-derived strain (XJCJ2301G) or a Shandong strain (ShX310). This study highlights the importance of monitoring cross-species transmission between cattle and goats, especially in the mountainous areas of Southwest China where mixed farming occurs, and thus, the monitoring of cross-species transmission between cattle and goats is important for preventing new public health challenges, providing important insights for research on cross-species transmission, early prevention, and control measures, with potential applications in vaccine development.